Do like a duck does - Hindley, Judy.; Bates, Ivan (Cambridge, MA : Candlewick Press, 2008)
By challenging a hairy stranger to imitate the behavior of herself and her ducklings, a mother duck proves that he is a fox and not a duck.
BR
Keywords: Ducks -- Fiction; Foxes -- Fiction; Stories in rhyme